Synthesis of mixed-dimensional 1D-graphene nanoribbon/2D-CuSe heterostructures with controllable band alignments - Yong Zhang; Jianchen Lu; Lei Gao; Xin-jing Zhao; Gefei Niu; Xi Geng; Yi Zhang; Shicheng Li; Yuhang Yang; Yuan-Zhi Tan; Shixuan Du; Jinming Cai (Nature Communications)
Abstract One- and two-dimensional (1D-2D) heterostructures have drawn growing interest due to their appealing optoelectronic and catalytic properties. Controlling the band alignment of 1D-2D heterostructures is crucial for their large-scale applications, but remains challenging to achieve experimentally. Here, we report a strategy for the atomically precise fabrication of 1D graphene nanoribbon (GNR) homojunctions and a variety of 1D-GNRs/2D-CuSe vertical heterostructures on Cu(111) substrate. By combining scanning tunneling microscopy, non-contact atomic force microscopy characterizations and density functional theory calculations, the entire preparative process is fully visualized. The GNR homojunctions, which bridge the Cu(111) substrate and the semiconducting CuSe monolayer, show a p-n junction characteristic. The hybrid heterostructures display various band alignments, achieved by varying the width and edge topologies of the GNRs, as well as controlling two different semiconducting phases of the CuSe monolayer. This work offers a promising method to precisely synthesize 1D/2D heterostructures with diverse band alignments for applications in high-performance nanodevices.